Evaluation of the ability of adjuvant tamoxifen‐benefit gene signatures to predict outcome of hormone‐naive estrogen receptor‐positive breast cancer patients treated with tamoxifen in the advanced setting. Issue 8 (10th July 2014) - Sieuwerts, Anieta M.; Lyng, Maria B.; Meijer-van Gelder, Marion E.; de Weerd, Vanja; Sweep, Fred C.G.J.; Foekens, John A.; Span, Paul N.; Martens, John W.M.; Ditzel, Henrik J.
Abstract : To identify molecular markers indicative of response to tamoxifen and easily implemented in the routine setting, we recently reported three gene signatures that could stratify post‐menopausal tamoxifen‐treated, estrogen receptor‐positive (ER+) patients according to outcome in the adjuvant setting. Here, we evaluated the predictive potential of the total of 14 genes included in the 3 gene signatures using 2 hormone‐naïve Dutch ER+ cohorts of a total of 285 recurrent breast cancer patients treated with first‐line tamoxifen. mRNA levels were measured by reverse transcriptase quantitative PCR (RT‐qPCR) and the length of progression‐free survival (PFS) was used as the primary endpoint. A Mann–Whitney U test was used to select for differentially expressed genes between tumors of patients who showed or did not show progressive disease within 6 months after start of tamoxifen treatment. Cox univariate and multivariate regression analysis for PFS were used to further assess their (independent) predictive potential. Five (BCAR3, BCL2, ESR1, IGF1R, and NCOA1) of the 14 genes analyzed showed significantly higher mRNA levels in tumors of patients who showed no disease progression within 6 months. Only BCAR3, BCL2 and NAT1 were significantly associated with a favorable PFS in multivariate analysis that included the traditional predictive factors: age, dominant relapse site, disease‐free interval, ER and progesterone receptor (PGR), and adjuvant chemotherapy. This study shows that BCAR3, BCL2 and NAT1 in particular exhibit predictive promise regarding the efficacy of tamoxifen treatment in recurrent disease, in addition to the previously shown favorable outcome in the adjuvant setting. Highlights: We recently published a promising predictive set of 14 genes for ER+ breast cancer. We investigated the performance of these 14 genes in a new clinical cohort. Three genes remained significant for both the adjuvant and 1st‐line clinical setting. These three genes were measured reliable and robust in different laboratories. Patients may benefit from the addition of BCAR3, BCL2 and NAT1 to standard measures.